Iatrogenic left circumflex vessel occlusion after minimal access mitral valve repair: the role of optical coherence tomography. Issue 5 (August 2017) - Abdelaziz, Hesham K.; Wiper, Andrew; Saravanan, Palanikumar; Zacharias, Joseph
Abstract : Supplemental Digital Content is available in the text.